NYPD Red 4 [large type] - Patterson, James, 1947-; Karp, Marshall (Patterson, James, 1947- NYPD red mystery., 2016)
An audacious jewel heist. A murdered actress. A killer case for NYPD Red. In a city where crime never sleeps, NYPD Red is the elite task force called in only when a case involves the rich, famous, and connected. Detective Zach Jordan and his partner, Kylie MacDonald--the woman who broke his heart at the police academy--are the best of the best, brilliant and tireless investigators who will stop at nothing to catch a criminal, even if it means antagonizing the same high-flying citizens they're supposed to be helping. When a glitzy movie premiere is the scene of a shocking murder and high-stakes robbery, NYPD Red gets the call. Traversing the city's highs and lows, from celebrity penthouses to the depths of Manhattan's criminal underworld, Zach and Kylie have to find a cold-blooded killer--before he strikes again.